2014
DOI: 10.1080/00423114.2013.877592
|View full text |Cite
|
Sign up to set email alerts
|

Wobble of a racing bicycle with a rider hands on and hands off the handlebar

Abstract: So far fundamental papers on the understanding of the wobble mode at motorcycles have been published, but in contrast, little research has been published on the wobble mode at bicycles. Wobble denotes a characteristic unstable oscillatory mode dominated by oscillations of the front wheel about the steering axis. The wobble mode of a trekking bicycle at low speeds has already been analysed, where no influence of the rider's hands on the steering system is taken into account. The wobble mode of a racing bicycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Notable is that he did not incorporate the twisting torque into the tyre model. In return, Plo¨chl et al 10 and Klinger et al 13 did include the twisting torque and found a significant effect of their tyre model on the capsize and weave mode. In agreement with the results presented in this article, they found that the capsize mode becomes stable and the weave mode significantly destabilizes by implementing the realistic tyre model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notable is that he did not incorporate the twisting torque into the tyre model. In return, Plo¨chl et al 10 and Klinger et al 13 did include the twisting torque and found a significant effect of their tyre model on the capsize and weave mode. In agreement with the results presented in this article, they found that the capsize mode becomes stable and the weave mode significantly destabilizes by implementing the realistic tyre model.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 However, modelling the rider's arms on the steer does drastically change the dynamic properties. 12,13 In Doria and Tognazzo, 12 it was reported that a small amount (25.7 N m/rad) of passive arm stiffness is able to destroy the stability by making the steer-roll combination ineffective. However, in Doria and Tognazzo, 12 tyre dynamics were not considered and this significantly changes the influence of the rider's impedance on the handlebars.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations